Parasitosis of Ruminant Animal in Private Farms of Vysokogorny and Laishevskiy Districts of the Republic of Tatarstan - R. I. Shangaraev; M. Kh. Lutfullin; N. A. Lutfullina (Российский паразитологический журнал)
The purpose of the research is to study the species composition of intestinal parasitosis agents in ruminant animals in citizens’ private farms in Vysokogorny and Laishevskiy districts of the Republic of Tatarstan. Materials and methods. The work has been executed in the Epizootology, Parasitology and Radiobiology Department at the Kazan State Academy of Veterinary Science named after N.E.Bauman and in citizens’ private farms in Vysokogorny and Laishevskiy districts of the Republic of Tatarstan during autumn-winter period in 2016-2017. 586 fecal specimen, including 364 samples of cattle, 168 samples of sheep and 54 samples of goats, have been studied by the modified method of flotation. Animals extent of invasion were determined as well as average number of helminth eggs and eimeria oocyst in 1 g of feces were calculated with the help of VIGIS count chamber. Kheisin key was used to identify eimeria types. Statistical analysis of numeric material was carried out with the help of Microsoft Excel spreadsheet processor. Results and discussion. Eggs of helminth classes Fasciola, Moniezia, Nematodirus, Trichocephalus as well as eimeria oocyst had been founded in cattle and small ruminants fecal specimen. On investigated areas the degree of infection by fascioles was 28.2%, by moniezia 41.5%, by nematodirus 52.7%, by trichocephalus 28.3%, and by eimeria 51.3%. Small ruminants were infected with fascioles in 56.5%, moniezia in 52.7%, thysaniezia in 15.7%, nematodirus in 58.1%, trichocephalus in 38.5%, and eimeria in 21.3%. Taking into consideration prevalence of parasitosis of ruminant animal in private farms of Vysokogorny and Laishevskiy districts of the Republic of Tatarstan it is necessary to make up a plan of antiparasitic measures inclusive of climate pattern and developmental biology of agents.